Socioeconomic Perspectives on Household Chestnut Fruit Utilization and Chestnut Blight Prevention Efforts in Turkey - Okan, Taner; Köse, Coşkun; Wall, Jeffrey (MDPI AG, 2017)
Exotic pathogens, within the center of genetic diversity for the species, compromise European chestnut populations in Turkey. In Turkey today, the species is of tremendous economic, ecological and cultural importance. At this time of severe exotic pathogenic pressure on a highly-valued forest species, we ask, how does awareness of diseases and treatments as well as value for chestnut trees affect the efforts of households to manage pests and diseases of chestnut trees in Turkey? We conducted 96 surveys in 34 villages in 10 provinces across Turkey to investigate awareness of diseases and other challenges to the chestnut population, chestnut harvesting habits, family value for chestnuts and efforts to mitigate pest and disease pressure. We analyze our results using cluster and regression analysis. Our results show that based on analysis of all observed characteristics, our research sites in Turkey break cleanly into groups based on production level. Further, results demonstrate significant correlation between amount of chestnut-derived income and awareness of pests and diseases as well as the likelihood of households enacting disease mitigation measures. These results also demonstrate correlation between observed awareness of diseases and pests and the likelihood of households enacting disease mitigation measures.
Keywords: Castanea sativa; non-wood forest products; forest disease mitigation; household economy